Developing a prototype micro hot embossing setup - Ali, Mohammad Yeakub; Ayob, Mohd Hafiz; Mohd Isa, Saiful Adzli (2005)
This paper discusses the development of a prototype of micro hot embossing setup. It included microtool, heating jig, temperature controller, cooling system, etc. The total cost was about few thousand USD. All these components were used with the help of a numerical control (NC) milling machine. The heating jig, heaters, controller, etc. were fixed on the table of the milling machine. The forming tool was held by a small chuck and that chuck was finally held with the bigger chuck of the milling machine. The microtool was moved by using the NC of the milling machine and the punching action was provided by the lever. The formed microcomponents were immediately cooled by aerosol to retain the final shape. At this first stage, a microtube with 0.9 mm internal diameter and 1.2 mm external diameter was used as a forming microtool. This prototype micro hot embossing setup was used on a sheet of polypropylene to emboss microhemisphere intended to use as microlens for various MEMS applications. The fabricated microcomponents were inspected by scanning electron microscope where some defects were identified as the forming process was not optimized yet. The prototype setup was found to work efficiently.